Political violence in Sri Lanka 1971-1987 - "Samaranayke,S.V.D. Gamini" (New Delhi, 2008)
This book is a revised version of my Ph.D. thesis submitted to the University of St. Andrews in 1991. The publication of this book was caught up in a certain controversy of perspectives and was therefore delayed in its publication. The subject of the book is obviously a topic which is of the greatest relevance currently to Sri Lanka.
Keywords: Political Violence